Case report: binaural beats music assessment experiment - Krasnoff, Elizabeth; Chevalier, Gaétan (Frontiers in Human Neuroscience, 2023)
We recruited subjects with the focus on people who were stressed and needed a break to experience relaxation. The study used inaudible binaural beats (BB) to measure the ability of BB to induce a relaxed state. We found through measuring brain wave activity that in fact BB seem to objectively induce a state of relaxation. We were able to see this across several scores, F3/F4 Alpha Assessment and CZ Theta Beta, calculated from EEG readings, that indicated an increase in positive outlook and a relaxing brain, respectively, and scalp topography maps. Most subjects also showed an improvement in Menlascan measurements of microcirculation or cardiovascular score, although the Menlascan scores and Big Five character assessment results were less conclusive. BB seem to have profound effects on the physiology of subjects and since the beats were not audible, these effects could not be attributed to the placebo effect. These results are encouraging in terms of developing musical products incorporating BB to affect human neural rhythms and corollary states of consciousness and warrant further research with more subjects and different frequencies of BB and different music tracks.